2019
DOI: 10.5114/wiitm.2019.89394
|View full text |Cite
|
Sign up to set email alerts
|

Coblation annuloplasty in cervical discogenic pain without radiculopathy.

Abstract: Introduction: The nerve fibers innervating the annulus fibrosus are the major origin of degeneration-associated discogenic pain. Coblation is a tissue-dissociating technique in which the nerve fibers in the degenerative disc tissue are ablated. We hypothesized that coblation annuloplasty would be an effective maneuver for cervical discogenic pain without radiculopathy. Aim: To observe the therapeutic efficacy of coblation annuloplasty in patients with cervical discogenic pain without radiculopathy. Material an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The measures were recorded preoperatively and 3, 6, 12 and 24 mo after surgery. Functional status was qualified as “excellent,” “good,” “fair” and “poor” according to the Modified Macnab criteria[ 19 ] and recorded at 3, 6, 12 and 24 mo postoperatively.…”
Section: Methodsmentioning
confidence: 99%
“…The measures were recorded preoperatively and 3, 6, 12 and 24 mo after surgery. Functional status was qualified as “excellent,” “good,” “fair” and “poor” according to the Modified Macnab criteria[ 19 ] and recorded at 3, 6, 12 and 24 mo postoperatively.…”
Section: Methodsmentioning
confidence: 99%
“…However, recent studies have shown that intervertebral discs, particularly degenerative ones, have extensive innervation. 8 In 1988, Bogduk et al described the innervation patterns of the sinuvertebral nerves into the outer third of the annulus fibrosis based on microdissection and histologic studies from clinical patients and cadavers. 10 Their research also demonstrated the presence of nerve fibers and nerve endings within the outer third of the annulus fibrosis using cholinesterase staining.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars once thought that the intervertebral disc was not innervated; therefore, the diagnosis of discogenic pain was controversial. However, recent studies have shown that intervertebral discs, particularly degenerative ones, have extensive innervation 8 . In 1988, Bogduk et al .…”
Section: Introductionmentioning
confidence: 99%